Society of Friends collection
Collection of Christian and brotherly advices (17th and 18th centuries) and notice containing excerpts from letters and minutes of meetings concerning marriage to kinsmen (1753) written for Friends in Pennsylvania and New Jersey; register of Friends visiting New England (1656-1796); photostats of a record book (1684-1755), letter (1754), and fragment of document pertaining to the Friends in Virginia; and a volume (undated) containing a price list of 18th and 19th century books concerning the Society of Friends.
In part, photostatic reproductions.
Microfilm edition of the volume titled, Collection of Christian and brotherly advices, available
Microfilm produced from originals in the Manuscript Division.
Religious group composed of individuals known as Quakers.
Collection material in English.
Keywords: Quakers; Society of Friends; Society of Friends -- New Jersey; Society of Friends -- Pennsylvania; Society of Friends -- Virginia; New Jersey -- Religious life and customs; Pennsylvania -- Religious life and customs; Virginia -- Religious life and customs